1991
DOI: 10.1021/ie00049a005
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive diffusion under catalytic hydroprocessing conditions

Abstract: The effect of the ratio of reactant molecular diameter to catalyst pore diameter on the restrictive diffusion of reactants in catalysts under catalytic hydroprocessing conditions was studied. Hydrogenation of four nitrogen-containing heterocyclic model compounds dissolved in decalin was carried out in a batch-mode operation at 623 K and 5.27 MPa of hydrogen partial pressure over three Ni-Mo/alumina catalysts encompassing a range of molecular to pore sizes of 0.03 to 0.35. An empirical correlation for restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
3
54
0
Order By: Relevance
“…Most of the investigators tried to correlate their diffusion data with the theoretical models developed for membranes. Some studies showed that their data could be well represented by the Renkin equation (Chantong and Massoth, 1983;Limbach and Wei, 1990;Tsai et al, 1991;Rhee and Guin, 1994), while others observed the agreement of their results with the Beck and Schultz's power law of different z values ranging from 3.5 to 5.2 (Chantong and Massoth, 1983;Spry and Sawyer, 1975;Cheng et al, 1990;Tsai et al, 1991;Lee et al, 1991;1991a). Guo et al (1990) On the other hand, due to the different pore structures between membranes and porous alumina and silica, some different results have been observed, and different hindered diffusion concepts were proposed.…”
Section: Hindered Diffusion In Alumina Silica and Porous Catalystsmentioning
confidence: 88%
See 2 more Smart Citations
“…Most of the investigators tried to correlate their diffusion data with the theoretical models developed for membranes. Some studies showed that their data could be well represented by the Renkin equation (Chantong and Massoth, 1983;Limbach and Wei, 1990;Tsai et al, 1991;Rhee and Guin, 1994), while others observed the agreement of their results with the Beck and Schultz's power law of different z values ranging from 3.5 to 5.2 (Chantong and Massoth, 1983;Spry and Sawyer, 1975;Cheng et al, 1990;Tsai et al, 1991;Lee et al, 1991;1991a). Guo et al (1990) On the other hand, due to the different pore structures between membranes and porous alumina and silica, some different results have been observed, and different hindered diffusion concepts were proposed.…”
Section: Hindered Diffusion In Alumina Silica and Porous Catalystsmentioning
confidence: 88%
“…Satterfield et al, 1973;Guin, 1994. Tsai et al, 1991;Lee et al, 1991;1991a;Chantong andMassoth, 1983. Davidson andDeen, 1988;Bohrer et al, 1984;Cannel1 and Rondelez, 1980.…”
Section: Do1mentioning
confidence: 99%
See 1 more Smart Citation
“…The following power-law relationship is one which has been used in hindered diffusion studies. 10,17 FðkÞ ¼ ð1 À kÞ m :…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (1991) estimated the effect of restricted diffusion in catalytic hydroprocessing. Limbach and Wei (1990) studied restricted diffusion of porphyrins in porous particles, and showed how best to estimate average pore and molecular sizes.…”
Section: Introductionmentioning
confidence: 99%